Spring‐Fall Asymmetry in VLF Amplitudes Recorded in the North Atlantic Region: The Fall‐Effect - Macotela, E.L.; Clilverd, M.; Renkwitz, T.; Chau, J.; Manninen, J.; Banyś, D. (Hoboken, NJ : Wiley, 2021)
A spring-fall asymmetry is observed in daytime amplitude values of very low frequency (VLF) radio wave signals propagating over the North Atlantic during 2011–2019. We explore the processes behind this asymmetry by comparing against mesospheric mean temperatures and the semidiurnal solar tide (S2) in mesospheric winds. The solar radiation influence on VLF subionospheric propagation was removed from the daytime VLF amplitude values, isolating the fall-effect. Similarly, the symmetric background level was removed from mesospheric mean temperatures undertaking comparable analysis. During fall, all three analyzed parameters experience significant deviation from their background levels. The VLF amplitude variation during spring is explained by the seasonal variation in solar illumination conditions, while the fall-effect can be interpreted as a mean zonal wind reversal associated with both a S2 enhancement, and temperature reductions. Decreases in temperature can produce decreases in collision frequency, reducing VLF signal absorption, driving the observed VLF asymmetry. publishedVersion